Rancang Bangun E-Repository Di Politeknik Negeri Balikpapan Untuk Mendukung Aktivitas Akademik Dan Penelitian - Kango, Riklan; Amsal, Andi Yasir; Ihsan, Ihsan; Nugrahandy, Reza (JST (Jurnal Sains Terapan), 2024)
E-Repository is a digital document storage and management system that has become the main focus in the higher education environment in this digital era. This research aims to design and implement an E-Repository at Politeknik Negeri Balikpapan with the primary objective of improving the accessibility of knowledge management in supporting academic and research activities. This research details the implementation steps, from requirement analysis to functionality testing. The result is an E-Repository that allows lecturers, students, and staff of Poltekba to easily store, search, and download digital documents related to academic and research activities. Implementing this E-Repository has created tangible benefits, including increased accessibility of educational resources. This research also evaluated the technological readiness of the E-Repository using the Technology Readiness Level (TRL). The evaluation result shows that the E-Repository at Politeknik Negeri Balikpapan reaches level 7 (system prototype demonstration in operational environment) on the TRL scale. Thus, this research provides a comprehensive view of the development and implementation of E-Repository in higher education environments.